PENGEMBANGAN AGRIBISNIS SEBAGAI STRATEGI PENANGGULANGAN KEMISKINAN DI PERDESAAN - Akhmadi Akhmadi; Hermanto Siregar; M Parulian Hutagaol (Jurnal Manajemen & Agribisnis, 2016)
Agribusiness and Rural Entrepreneurship Development Program (PUAP) is one of the poverty reduction programs in rural areas under the coordination of the National Program for Community Empowerment. PUAP program provides capital assistances for farmer group members i.e. land owning farmers, tenant farmers, farm laborers, and farm households coordinated by the Joint Farmers Group. The objective of this study was to formulate the best strategy to overcome poverty in rural areas. The analytical methods utilized in this were Double Difference and Quantitative Strategic Planning Matrix (QSPM) analyses. The results showed that PUAP program has a significant impact on an increase in rice production per hectare and in income of farmers in Jati village respectively reaching up to 641.14 kg and Rp 878.358 larger than those in Jamali village in which PUAP program was not applied. Thus, QSPM analysis was carried out by an elaboration of eight key strategies with internal and external strategic factors to achieve the best strategy. The calculation result of Total Attractiveness Scores (TAS) showed that the strategy to strengthen human resources and institutional farmers through a special education program for agribusiness management development for farmers is perceived to be the most efficient strategy.Keywords: poverty, rural, PUAP, TAS, QSPMABSTRAKProgram Pengembangan Usaha Agribisnis Perdesaan (PUAP) merupakan salah satu program pengurangan kemiskinan di perdesaan di bawah koordinasi Program Nasional Pemberdayaan Masyarakat Mandiri sebagai program pemberdayaan masyarakat. Program PUAP memberikan bantuan modal usaha bagi petani anggota kelompok tani, baik petani pemilik, petani penggarap, buruh tani, maupun rumahtangga tani yang dikoordinasikan oleh Gabungan Kelompok Tani. Tujuan penelitian ini adalah untuk memformulasikan strategi terbaik penanggulangan kemiskinan di perdesaan. Metode analisis dalam pnelitian ini menggunakan analisis Double Difference dan analisis Quantitative Strategic Planning Matrix (QSPM). Hasilnya menunjukkan bahwa program PUAP telah memberikan dampak signifikan terhadap peningkatan produksi padi per hektar dan pendapatan petani di Desa Jati masing-masing sebesar 641,14 kg dan Rp878.358 lebih besar dibandingkan dengan produksi padi dan pendapatan petani di Desa Jamali yang tidak menerima Program PUAP. Hasil analisis QSPM, yaitu dengan mengelaborasikan delapan strategi kunci tersebut dengan faktor-faktor strategis internal dan eksternal untuk mendapatkan strategi yang terbaik.  Hasil perhitungan Total Attractiveness Scores (TAS) menunjukkan bahwa strategi penguatan sumberdaya manusia dan kelembagaan petani melalui program pendidikan khusus pengembangan manajemen agribisnis bagi petani adalah strategi yang terbaik. Kata kunci: kemiskinan, perdesaan, PUAP, TAS, QSPM